Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

From awareness of correctional services to accepting ex-prisoners among the public - Chau-Kiu Cheung; Wing Hong Chui (The Social Science Journal, 2026)

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

Deciphering the flavor chemistry of traditional and novel nattos: A multidisciplinary approach integrating amino acid profiling, volatile compound analysis, and molecular docking - Qile Zhang; Jiawei Wu; Yiu Ming Cheung; Yuhong Lin; Xinyi Deng; Minghui Li; Chufeng He; Dianjing Guo; Cheng Li; Hon Ming Lam; Wing Tak Wong (Food and Humanity, 2026)

Chronoregulatory and neuroprotective effects of yeast β-glucan against systemic inflammation - Wai-Yin Cheng; Pak-Hei Chan; Po-Lam Chan; Ka-Lung Lam; Nathanael Chun-Him Lai; Yuen-Shan Ho; Wing-Fai Yeung; Ka-Hing Wong; Peter Chi-Keung Cheung; Raymond Chuen-Chung Chang (Carbohydrate Polymers, 2026)

Periodic Water Level Anomalies over Coast of Guangdong Due to Tide–Wind Interaction over Taiwan Shoal - Wing-Kai Cheung; Tsun Shen; Kwan-Yi Tam; Ching-Chi Lam; Pak-Wai Chan; Chunjian Sun (Journal of Marine Science and Engineering, 2026)
The northeast monsoon prevailing over southeastern China in late seasons, generally from October to March, frequently generates water level anomalies upstream of the Taiwan Strait (TWS) that reach the coastal waters of Guangdong in South China, and, with compounding astronomical high tides, elevate coastal flood risk over the region. The risk of coastal flooding or sea inundation is further heightened when monsoon forcing co-occurs with storm surge brought by late-season tropical cyclones (TCs). This study integrates tide gauge observations from Hong Kong (HK) and its vicinity together with Delft3D Flexible Mesh simulations to diagnose a tide-modulated anomaly wave mechanism. Observations show that anomalies originating in or near TWS arrive in HK with station-dependent phasing. These water level anomalies exhibit a characteristic ~6 h periodicity west of the Taiwan Shoal, and display peaks that systematically align with the astronomical high tide. Time–frequency analysis reveals a wave period transformation from ~12 h north of Dongshandao over the coast of southeastern China to ~6 h west of the Taiwan Shoal. We test the hypothesis that wind-forced water anomalies generated in or near TWS undergo shoal-modulated nonlinear tide–wind interaction and tidal-current advection that transform their dominant period and phase-lock them to the tide, producing four anomaly peaks per day downstream and station-dependent phasing in HK. Hindcasts of the November 2024 monsoon episode reproduce the observed timing, periodicity, and spatial transition, while constituent experiments demonstrate that semi-diurnal forcing entering via the TWS is the primary driver of the ~6 h signal, with the Taiwan Shoal acting as the modulation locus. Accurate water level forecasts for the Guangdong coast, therefore, need to incorporate upstream wind forcing over the TWS and bathymetric controls around the Taiwan Shoal, with practical implications for compound flood risk during spring tides and co-occurring monsoon and/or TC events.

Genomic epidemiology and antimicrobial resistance of nontyphoidal Salmonella in retail meats in Hong Kong: A comprehensive surveillance study using whole-genome sequencing - Ivan Tak-Fai Wong; Iain Chi-Fung Ng; Dorothy Hong-Ting Cheung; Wing-Yin Tam; Choi-Ying Wong; Sharon Ka-Yee Fung; Ho-Ching Tong; Shue-Kei Chan; Tsz-Ying Wu; Elaine Yin-Ting Yeung; Jiaying Zhang; Franklin Wang-Ngai Chow; et al. (Food Research International, 2026)

Starch-EGCG complex enhances EGCG bioavailability through microbial metabolism and ameliorates metabolic-associated fatty liver disease via gut-liver axis - Zhengming Zhou; Lei Li; Juan Duan; Jian Zhu; Xinyuan Wang; Jiankui Guo; Ke Li; Lei Shi; Wing Tak Wong; Peter C.K. Cheung; Zhenyu Chen; Wen Hu; et al. (Carbohydrate Polymers, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Amelioration of MASLD via umbelliferone through modulation of hepatic metabolic function and restoration of gut-liver axis homeostasis - Qile Zhang; Yiu Ming Cheung; Chufeng He; Hoi Wa Yeung; Minghui Li; Xiao Yu Tian; Wing Tak Wong (Food Bioscience, 2026)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Exploring motor unit and neuromuscular junction dysfunction in aging and sarcopenia: insights from electromyography in systematic review - Can Cui; Yong Hu; Ronald Man Yeung Wong; Ning Zhang; Yuzhou Guan; Wing-hoi Cheung (GeroScience, 2025)

Study on the adsorption of common antibiotics in water by cellulose-based adsorbents derived from sugarcane bagasse - Jiarong Jin; Xuliang Lin; Chak Yin Tang; Wing Cheung Law; Ruchun Wu; Lei Zhong (Process Safety and Environmental Protection, 2025)

State of microbeads in facial scrubs: persistence and the need for broader regulation - Christelle Not; Kayi Chan; Mandy Wing Kwan So; Woody Lau; Lilia Tsz-Wing Tang; Coco Ka Hei Cheung (Environmental Science and Pollution Research, 2025)
Microbeads are small spherical plastic particles used as exfoliants in personal care products. Unfortunately, they have been found in the marine environment and are considered a significant contributor to global plastic pollution. In response, several countries have implemented microbead bans over the last few years. Here, we examined the exfoliant (scrubbing particles) composition of 28 facial scrubs from different regions in the presence and absence of microbead bans. We identified that over half of the exfoliant types identified in this study are microbeads, revealing the persistence of microbeads across various stages of microbead ban implementation. In regions with full bans, six out of eight products still contain microbeads, with some containing up to 6298 ± 1543 beads per gram of facial wash, suggesting the need for stronger legislation enforcement. We also identified challenges in distinguishing between microbeads composed of conventional plastics and synthetic waxes by Fourier-transform infrared spectroscopy. This study highlights the need to broaden the scope of microbead bans to include synthetic waxes, as they are not currently regulated. These findings underscore the importance of a broader and clearly articulated definition of microbeads in legislation to guide industry formulation and consumer choice of microbead-free products.

Anthropogenic marine debris accumulation and its ecological impact on the highly urbanized mangroves of Hong Kong - Lyle Dennis Vorsatz; Mandy Wing Kwan So; Chun On Cheung; Christelle Not; Stefano Cannicci (Marine Pollution Bulletin, 2025)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

An examination of the trade in bear parts and derivatives for traditional medicine in Hong Kong and its legality - Lalita Gomez; Jovy Y. S. Chan; Leni H. T. Cheung; Sze-Wing Chan; Chris R. Shepherd (European Journal of Wildlife Research, 2024)

A poly(o‐phenylenediamine) coated aluminum garter spring micro-solid phase extractor for pyrethroids in chili - Kednipa Lumlong; Charinrat Siritham; Wing Cheung Mak; Proespichaya Kanatharana; Panote Thavarungkul; Chongdee Thammakhet-Buranachai (Food Chemistry, 2024)

The Cell Permeant Phosphopetpide mimetic of VASP Alleviates Motor Function Deficits After Experimental Subarachnoid Hemorrhage - Madeleine Morelli; Jamie Adcock; Tsz Wing Yim; Jerri Rook; J. Mocco; Colleen Brophy; Joyce Cheung-Flynn (Journal of Molecular Neuroscience, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

The photometric observation of the quasi-simultaneous mutual eclipse and occultation between Europa and Ganymede on 22 August 2021 - Chu Wing So; Godfrey Ho Ching Luk; Giann On Ching Chung; Po Kin Leung; Kenneith Ho Keung Hui; Jack Lap Chung Cheung; Ka Wo Chan; Edwin Lok Hei Yuen; Lawrence Wai Kwan Lee; Patrick Kai Ip Lau; Gloria Wing Shan Cheung; Prince Chun Lam Chan; et al. (Icarus, 2023)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Feasibility of Sijunzi Tang (Chinese medicine) to enhance protein disulfide isomerase activities for reactivating malate dehydrogenase deactivated by polycyclic aromatic hydrocarbons - Ho Man Leung; Francis Siu Lai Kwok; Wing Yin Mo; Kwai Chung Cheung; Yik Kit Yue; Yee Keung Wong; Chi Kin Au; Martin Tsz Ki Tsui; Ken Kin Lam Yung (Environmental Science and Pollution Research, 2021)

Analgesic Effects of Cannabinoids for Chronic Non-cancer Pain: a Systematic Review and Meta-Analysis with Meta-Regression - Stanley Sau Ching Wong; Wing Shing Chan; Chi Wai Cheung (Journal of Neuroimmune Pharmacology, 2020)

Male-biased fasting-induced changes in hepatic tauro-cholic acid and plasma cholesterol in Sult2a8-haplodeficient mice - Kai Wang; Martin Yan-Chun Chan; Jian Xu; Pik-Shan Li; Xing Liu; Angus Yiu-Fai Lee; Susanna Sau-Tuen Lee; Wing-Tai Cheung (Transgenic Research, 2020)

Phenotypic characteristics of commonly used inbred mouse strains - Wing Yip Tam; Kwok-Kuen Cheung (Journal of Molecular Medicine, 2020)

Behavioural toxicity studies of Cyclope neritea and Nassarius mutabilis exposed to polycyclic aromatic hydrocarbons - Ho Man Leung; Patrick Ying Kit Yue; Stephen Cho Wing Sze; Chi Kin Au; Kwai Chung Cheung; Ka Loi Chan; Ho Yiu Lok; Wai Chin Li; Ken Kin Lam Yung (Environmental Science and Pollution Research, 2020)

The potential of Mikania micrantha (Chinese creeper) to hyperaccumulate heavy metals in soil contaminated by electronic waste - Ho Man Leung; Patrick Ying Kit Yue; Stephen Cho Wing Sze; Chi Kin Au; Kwai Chung Cheung; Ka Loi Chan; Kin Lam Ken Yung; Wai Chin Li (Environmental Science and Pollution Research, 2019)

Retrospective Study of the Characteristics of Anticoagulant-Type Rodenticide Poisoning in Hong Kong - Wai Yan Ng; Chor Kwan Ching; Yeow Kuan Chong; Sau Wah Ng; Wing Lan Cheung; Tony Wing Lai Mak (Journal of Medical Toxicology, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

Collating Historic Weather Observations for the East Asian Region: Challenges, Solutions, and Reanalyses - Fiona Williamson; Rob Allan; Guoyu Ren; Tsz-cheung Lee; Wing-hong Lui; Hisayuki Kubota; Jun Matsumoto; Jürg Luterbacher; Clive Wilkinson; Kevin Wood (Advances in Atmospheric Sciences, 2018)

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Wayne E. Clarke; Erin E. Higgins; Joerg Plieske; Ralf Wieseke; Christine Sidebottom; Yogendra Khedikar; Jacqueline Batley; Dave Edwards; Jinling Meng; Ruiyuan Li; Cynthia Taylor Lawley; Jérôme Pauquet; et al. (Theoretical and Applied Genetics, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Food wastes as fish feeds for polyculture of low-trophic-level fish: bioaccumulation and health risk assessments of heavy metals in the cultured fish - Zhang Cheng; Cheung-Lung Lam; Wing-Yin Mo; Xiang-Ping Nie; Wai-Ming Choi; Yu-Bon Man; Ming-Hung Wong (Environmental Science and Pollution Research, 2016)

Environmental mercury concentrations in cultured low-trophic-level fish using food waste-based diets - Zhang Cheng; Wing Yin Mo; Yu Bon Man; Cheung Lung Lam; Wai Ming Choi; Xiang Ping Nie; Yi Hui Liu; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

pIMP-PH114 Carrying bla IMP-4 in a Klebsiella pneumoniae Strain is Closely Related to Other Multidrug-Resistant IncA/C2 Plasmids - Pak-Leung Ho; Wai-U Lo; Jane Chan; Yuk-Yam Cheung; Kin-Hung Chow; Wing-Cheong Yam; Chi-Ho Lin; Tak-Lun Que (Current Microbiology, 2014)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Nanoparticle Based Galectin-1 Gene Silencing, Implications in Methamphetamine Regulation of HIV-1 Infection in Monocyte Derived Macrophages - Jessica L. Reynolds; Wing Cheung Law; Supriya D. Mahajan; Ravikumar Aalinkeel; Bindukumar Nair; Donald E. Sykes; Ken-Tye Yong; Rui Hui; Paras N. Prasad; Stanley A. Schwartz (Journal of Neuroimmune Pharmacology, 2012)

Fluorescence Imaging of the Lymph Node Uptake of Proteins in Mice after Subcutaneous Injection: Molecular Weight Dependence - Fang Wu; Suraj G. Bhansali; Wing Cheung Law; Earl J. Bergey; Paras N. Prasad; Marilyn E. Morris (Pharmaceutical Research, 2012)

Novel nonsense CDC73 mutations in Chinese patients with parathyroid tumors - Wai Kwan Siu; Chun Yiu Law; Ching Wan Lam; Chloe Miu Mak; Gary Wing Kin Wong; Andrew Yiu Yan Ho; Kwok Yip Ho; Ka Tai Loo; Sin Chuen Chiu; Louis Tsun Cheung Chow; Sui Fan Tong; Albert Yan Wo Chan (Familial Cancer, 2011)

The pharmacokinetic profile of recombinant human erythropoietin is unchanged in patients undergoing cardiac surgery - Stuart A. McCluskey; Wing K. Cheung; Rita Katznelson; Humara Poonawala; Ludwik Fedorko; George Djaiani; Bobby Mehta; Keyvan Karkouti (European Journal of Clinical Pharmacology, 2009)

Expression of SARS-coronavirus spike glycoprotein in Pichia pastoris - Chi-Pang Chuck; Chi-Hang Wong; Larry Ming-Cheung Chow; Kwok-Pui Fung; Mary Miu-Yee Waye; Stephen Kwok-Wing Tsui (Virus Genes, 2009)

Trends and spatial distribution of annual and seasonal rainfall in Ethiopia - Wing H. Cheung; Gabriel B. Senay; Ashbindu Singh (International Journal of Climatology, 2008)
As a country whose economy is heavily dependent on low‐productivity rainfed agriculture, rainfall trends are often cited as one of the more important factors in explaining various socio‐economic problems such as food insecurity. Therefore, in order to help policymakers and developers make more informed decisions, this study investigated the temporal dynamics of rainfall and its spatial distribution within Ethiopia. Changes in rainfall were examined using data from 134 stations in 13 watersheds between 1960 and 2002. The variability and trends in seasonal and annual rainfall were analysed at the watershed scale with data (1) from all available years, and (2) excluding years that lacked observations from at least 25% of the gauges. Similar analyses were also performed at the gauge, regional, and national levels. By regressing annual watershed rainfall on time, results from the one‐sample t ‐test show no significant changes in rainfall for any of the watersheds examined. However, in our regressions of seasonal rainfall averages against time, we found a significant decline in June to September rainfall (i.e. Kiremt) for the Baro‐Akobo, Omo‐Ghibe, Rift Valley, and Southern Blue Nile watersheds located in the southwestern and central parts of Ethiopia. While the gauge level analysis showed that certain gauge stations experienced recent changes in rainfall, these trends are not necessarily reflected at the watershed or regional levels. Copyright © 2008 Royal Meteorological Society

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The pharmacokinetics of erythropoietin in the cerebrospinal fluid after intravenous administration of recombinant human erythropoietin - Anargyros Xenocostas; Wing K. Cheung; Francis Farrell; Cindy Zakszewski; Marian Kelley; Andrzej Lutynski; Michael Crump; Jeffrey H. Lipton; Thomas L. Kiss; Catherine Y. Lau; Hans A. Messner (European Journal of Clinical Pharmacology, 2005)

Expression of TRPC homologs in endothelial cells and smooth muscle layers of human arteries - Ham Yip; Wing-Yee Chan; Pan-Cheung Leung; Hiu-Yee Kwan; Cuiling Liu; Yu Huang; Villaz Michel; David Tai-Wai Yew; Xiaoqiang Yao (Histochemistry and Cell Biology, 2004)

Pharmacokinetics and pharmacodynamics of epoetin alfa once weekly and three times weekly - Wing Cheung; Neil Minton; Kulasiri Gunawardena (European Journal of Clinical Pharmacology, 2001)